1969
DOI: 10.1063/1.1692411
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Injection and Containment of Electron Clouds in a Toroidal Apparatus

Abstract: Injection and containment of unneutralized clouds of electrons has been accomplished with an azimuthally symmetric, toroidal, magnetic field. The confining magnetic field is produced within a conducting toroidal chamber. The induction of this magnetic field has been used to inject the electron cloud (inductive charging). Average electron densities of 4 × 109 cm−3 and peak electrostatic well depths of ≈ 400 kV have been achieved. Semiempirical correlations are given which show the inductive charging scheme to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 12 publications
3
54
0
Order By: Relevance
“…Under certain restrictions, the equilibria are also expected to be stable [5,6,7]. Experiments confirm the existence of equilibria [8,9,10,11], but to date, no experiment has tested the theory closely.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Under certain restrictions, the equilibria are also expected to be stable [5,6,7]. Experiments confirm the existence of equilibria [8,9,10,11], but to date, no experiment has tested the theory closely.…”
Section: Introductionmentioning
confidence: 86%
“…Controlled injection of charge into the toroidal field is a significant initial hurdle to successful trapping of a nonneutral plasma. Past experimenters focused significant effort toward solving this problem [8,9,10,11], but none of them achieved the kind of reproducible initial charge distributions routinely obtained in cylindrical traps. The present experiment provides controlled charge injection by limiting the confinement region to a 'C'-shaped segment of the torus.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on nonneutral plasmas have been conducted on various machines such as the Penning trap [1], the Paul trap [2], and toroidal devices [3]. Recently, toroidal nonneutral plasmas confined on helical magnetic surfaces (HMSes) have been conducted [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A pure electron plasma can be confined in RT-1; the density is of the order of 10 11 m −3 , and the confinement time is longer than 400 s [3]. A toroidal system [4][5][6][7][8][9][10][11][12][13][14] has merits in trapping various kinds of charged particles including antimatters [15][16][17][18]. In our previous experiment on the Proto-RT device [6][7][8], we measured the internal electric potential by inserting probes and showed that an appropriate control of the potential of the internal ring produces closed equi-potential surfaces aligned with the magnetic surfaces, achieving good confinement.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, multiple wall probes [4] were used for perturbation-free diagnostics of radial electric field strength and spatial profiles of the plasma, as well as electrostatic fluctuation measurements in RT-1. To minimize electrostatic perturbations, image currents were measured using current amplifiers, where there were no voltage differences between the walls and the chamber.…”
Section: Introductionmentioning
confidence: 99%